1988
DOI: 10.1111/j.1365-2125.1988.tb03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of nitrendipine on the pharmacokinetics and pharmacodynamics of midazolam during steady state.

Abstract: and lInstitute of Psychosomatic Research, Herbsthalde 11, 7000 Stuttgart 1 FRG 1 The possible interaction (as indicated by rat experiments) between calcium channel blocking agents and benzodiazepines has been evaluated in nine healthy subjects. 2 Subsequently to an intravenous loading dose (0.07 mg kg-1) midazolam was infused for 6 h (0.035 mg kg-' h-1) and steady state plasma levels between 54 to 114 ,ug 1-1 were achieved. Two hours after the bolus of midazolam a solution of 20 mg nitrendipine or placebo was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…This pattern was known from different studies conducted with midazolam (Handel et al, 1988;Klotz et al, 1985), as well as other BZD (Sittig et al, 1982). Additionally, the increased sedation index and reported side effects such as fatigue and amnesia, indicate the typical agonist BZD action.…”
Section: Discussionmentioning
confidence: 95%
“…This pattern was known from different studies conducted with midazolam (Handel et al, 1988;Klotz et al, 1985), as well as other BZD (Sittig et al, 1982). Additionally, the increased sedation index and reported side effects such as fatigue and amnesia, indicate the typical agonist BZD action.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, objective evaluation such as number of cough and subjective evaluation such as the ease of performing the examination by the bron-choscopist would be also important to assess feasibility. Although patients' full recovery from sedation was not defined in this study, one study reported that half-life of midazolam is about 2.5 h 22) . Therefore, most of the patients were considered to have recovered almost completely enough to reply to questionnaires.…”
Section: Discussionmentioning
confidence: 94%
“…Benzodiazepines are reported to confer a high risk of teratogenic effects in foetuses when used during pregnancy (Wikner et al, 2007). These drugs are known to have a short half-life of 2 hr in human adults and are easily eliminated from the body (Eberts et al, 1981;Klotz et al, 1985;Handel et al, 1988). Specifically, they are rapidly metabolized into the 1'-OH or 4'-OH form, primarily by CYP3A4 in the human liver or CYP3A11 in the mouse liver (Kronbach et al, 1989;Thummel and Wilkinson, 1998;Hyland et al, 2009).…”
Section: Introductionmentioning
confidence: 99%